Non-aqueous electrolyte secondary battery

By setting two graphite particle layers on the negative electrode mixture layer to adjust the void ratio and filling density between the graphite particles, the problems of electrolyte circulation permeability and battery capacity are solved, and high capacity and stable fast charging cycle characteristics are achieved.

CN114730862BActive Publication Date: 2025-01-10PANASONIC ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080081687.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-27
Filing Date
2020-11-19
Publication Date
2025-01-10
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

When the existing nonaqueous electrolyte secondary batteries increase the filling density of the negative electrode active substance, the liquid circulation permeability of the electrolyte solution becomes worse, resulting in a decrease in the fast charging cycle characteristics and a lower battery capacity.

Method used

By providing two graphite particle layers on the negative electrode mixture layer, the inter-population ratio between graphite particles in the second layer is higher than that of the first layer and the filling density is slightly lower. The inter-population ratio between graphite particles is controlled to be 1.1-2.0 and the filling density ratio is 0.9 ~1.1 to improve electrolyte circulation permeability and battery capacity.

Benefits of technology

A high-capacity nonaqueous electrolyte secondary battery is realized, and the reduction of fast charging cycle characteristics is suppressed, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114730862B_ABST
    Figure CN114730862B_ABST
Patent Text Reader

Abstract

The purpose of the present application is to provide an excellent non-aqueous electrolyte secondary battery with high capacity and suppressed reduction in rapid charge cycle characteristics. As one embodiment of the present application, the non-aqueous electrolyte secondary battery has a negative electrode, wherein the negative electrode has: a negative electrode collector, a first negative electrode mixture layer disposed on the surface of the negative electrode collector, and a second negative electrode mixture layer disposed on the surface of the first negative electrode mixture layer, wherein the first negative electrode mixture layer and the second negative electrode mixture layer contain graphite particles, and the ratio (S2 / S1) of the void ratio (S2) between the graphite particles in the second negative electrode mixture layer to the void ratio (S1) between the graphite particles in the first negative electrode mixture layer is 1.1 to 2.0, and the ratio (D2 / D1) of the packing density (D2) of the second negative electrode mixture layer to the packing density (D1) of the first negative electrode mixture layer is 0.9 to 1.1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries using graphite particles as negative electrode active materials are widely used as secondary batteries with high energy density. By increasing the packing density of the negative electrode active material in the negative electrode mixture layer, the battery capacity can be increased. However, if the amount of negative electrode active material per unit volume is increased to increase the packing density, the gaps between the negative electrode active materials become smaller, the liquid circulation permeability of the electrolyte becomes worse and decreases, and there is a problem that the battery capacity decreases due to repeated rapid charging.

[0003] For example, in the inventions disclosed in Patent Documents 1 to 3, the filling density of the negative electrode active material is made lower on the outer surface side than on the collector side in the negative electrode mixture layer, thereby increasing the gap between the negative electrode active materials on the outer surface side and improving the liquid circulation permeability of the electrolyte. However, the amount of negative electrode active material per unit volume in the negative electrode mixture layer decreases, so there is a problem of reduced battery capacity.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-77463

[0007] Patent Document 2: Japanese Patent Application Publication No. 2006-196457

[0008] Patent Document 3: Japanese Patent Application No. 2015-511389 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Therefore, an object of the present application is to provide an excellent nonaqueous electrolyte secondary battery having a high capacity and in which a decrease in rapid charge cycle characteristics is suppressed.

[0011] Means used to solve problems

[0012] A non-aqueous electrolyte secondary battery as one embodiment of the present application is characterized in that it comprises a negative electrode, wherein the negative electrode has a negative electrode collector, a first negative electrode mixture layer arranged on the surface of the negative electrode collector, and a second negative electrode mixture layer arranged on the surface of the first negative electrode mixture layer, the first negative electrode mixture layer and the second negative electrode mixture layer contain graphite particles, the ratio (S2 / S1) of the void fraction (S2) between the graphite particles in the second negative electrode mixture layer to the void fraction (S1) between the graphite particles in the first negative electrode mixture layer is 1.1 to 2.0, and the ratio (D2 / D1) of the packing density (D2) of the second negative electrode mixture layer to the packing density (D1) of the first negative electrode mixture layer is 0.9 to 1.1.

[0013] Effects of the Invention

[0014] According to one embodiment of the present application, it is possible to provide an excellent nonaqueous electrolyte secondary battery having a high capacity and capable of suppressing a decrease in rapid charge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is an axial cross-sectional view of a cylindrical secondary battery as an example of an embodiment.

[0016] Figure 2 It is a cross-sectional view of a negative electrode as an example of an embodiment. DETAILED DESCRIPTION

[0017] As described above, in existing batteries, it is difficult to achieve both high capacity and suppression of excellent rapid charge cycle characteristics. Therefore, the inventors conducted in-depth research and found that the void ratio between the graphite particles on the outer surface side can be increased by including graphite particles with low internal porosity on the outer surface side of the negative electrode mixture layer, and the packing density can be maintained at about the same level as that on the negative electrode collector side, thereby conceiving of a non-aqueous electrolyte secondary battery with high capacity and suppression of the reduction of rapid charge cycle characteristics, which is excellent and shown below.

[0018] A non-aqueous electrolyte secondary battery as one embodiment of the present application is characterized in that it comprises a negative electrode, wherein the negative electrode comprises: a negative electrode collector, a first negative electrode mixture layer arranged on the surface of the negative electrode collector, and a second negative electrode mixture layer arranged on the surface of the first negative electrode mixture layer, the first negative electrode mixture layer and the second negative electrode mixture layer contain graphite particles, the ratio (S2 / S1) of the void fraction (S2) between the graphite particles in the second negative electrode mixture layer to the void fraction (S1) between the graphite particles in the first negative electrode mixture layer is 1.1 to 2.0, and the ratio (D2 / D1) of the packing density (D2) of the second negative electrode mixture layer to the packing density (D1) of the first negative electrode mixture layer is 0.9 to 1.1.

[0019] Hereinafter, an example of an embodiment of a cylindrical secondary battery of the present application is described in detail with reference to the accompanying drawings. In the following description, specific shapes, materials, numerical values, directions, etc. are only examples for easy understanding of the present invention and may be appropriately changed according to the specifications of the cylindrical secondary battery. In addition, the outer casing is not limited to a cylindrical shape, for example, it may also be a square shape, etc. In addition, in the following description, when multiple embodiments and variations are included, it is envisaged from the beginning that their characteristic parts may be appropriately combined and used.

[0020] Figure 1 It is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 In the secondary battery 10 shown, an electrode body 14 and a nonaqueous electrolyte (not shown) are housed in an outer casing 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. It should be noted that, hereinafter, for convenience of description, the sealing body 16 side is set as "upper" and the bottom side of the outer casing 15 is set as "lower".

[0021] The interior of the secondary battery 10 is sealed by sealing the open end of the outer body 15 with a sealing body 16. Insulating plates 17 and 18 are respectively provided above and below the electrode body 14. The positive lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the bottom plate of the sealing body 16, that is, the lower surface of the filter 22. In the secondary battery 10, the top plate of the sealing body 16, that is, the cover 26, which is electrically connected to the filter 22, becomes the positive terminal. On the other hand, the negative lead 20 extends to the bottom side of the outer body 15 through the through hole of the insulating plate 18 and is welded to the bottom inner surface of the outer body 15. In the secondary battery 10, the outer body 15 becomes the negative terminal. It should be noted that when the negative lead 20 is provided at the terminal portion, the negative lead 20 extends to the bottom side of the outer body 15 through the outside of the insulating plate 18 and is welded to the bottom inner surface of the outer body 15.

[0022] The outer body 15 is, for example, a metal outer can with a bottomed cylindrical shape. A gasket 27 is provided between the outer body 15 and the sealing body 16 to ensure the airtightness inside the secondary battery 10. The outer body 15 has, for example, a groove portion 21 formed by pressing the side surface from the outside to support the sealing body 16. The groove portion 21 is preferably formed in an annular shape along the circumference of the outer body 15, and supports the sealing body 16 on its upper surface via the gasket 27.

[0023] The sealing body 16 has a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25 and a cover 26 stacked in sequence from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and the insulating member 24 is sandwiched between their respective peripheral portions. If the internal pressure of the battery rises due to abnormal heat, for example, the lower valve body 23 breaks, whereby the upper valve body 25 bulges toward the cover 26 side and separates from the lower valve body 23, and the electrical connection between the two is cut off. If the internal pressure rises further, the upper valve body 25 breaks, and the gas is discharged from the opening 26a of the cover 26.

[0024] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , in particular, the negative electrode active material contained in the negative electrode mixture layer 32 constituting the negative electrode 12 will be described in detail.

[0025] [negative electrode]

[0026] Figure 2 1 is a cross-sectional view of a negative electrode 12 as an example of an embodiment. The negative electrode 12 includes: a negative electrode current collector 30, a first negative electrode mixture layer 32a provided on the surface of the negative electrode current collector 30, and a second negative electrode mixture layer 32b provided on the surface of the first negative electrode mixture layer 32a. The thickness of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b may be the same or different. The ratio of the thickness of the first negative electrode mixture layer 32a to the second negative electrode mixture layer 32b is, for example, 3:7 to 7:3, preferably 4:6 to 6:4, and more preferably 5:5 to 6:4.

[0027] The negative electrode current collector 30 is made of, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface. The thickness of the negative electrode current collector 30 is, for example, 5 μm to 30 μm.

[0028] The first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b (hereinafter, the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b are sometimes collectively referred to as the negative electrode mixture layer 32) contain graphite particles. In addition, the negative electrode mixture layer 32 preferably contains a binder, etc. As a binder, for example, there can be mentioned: fluorine resin, PAN, polyimide resin, acrylic resin, polyolefin resin, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (PAA-Na, PAA-K, etc., and can also be a partially neutralized salt), polyvinyl alcohol (PVA), etc. They can be used alone or in combination of two or more.

[0029] The graphite particles used in the present embodiment include natural graphite, artificial graphite, and the like. The interplanar spacing (d 002 ) is preferably 0.3354 nm or more, more preferably 0.3357 nm or more, and is preferably less than 0.340 nm, and more preferably 0.338 nm or less. In addition, the crystallite size (Lc(002)) of the graphite particles used in the present embodiment determined by X-ray diffraction is preferably 5 nm or more, more preferably 10 nm or more, and is preferably 300 nm or less, and more preferably 200 nm or less. The interplanar spacing (d 002 When the crystallite size (Lc(002)) and the crystallite size (Lc(002)) satisfy the above ranges, the battery capacity of the secondary battery 10 tends to be larger than when the above ranges are not satisfied.

[0030] The graphite particles contained in the first negative electrode mixture layer 32a can be made, for example, as described below. The coke (precursor) to be the main raw material is crushed into a specified size, and after agglomerating them with a binder, they are further pressed into a block state and fired at a temperature of 2600°C or above to graphitize them. The block-shaped molded body after graphitization is crushed and sieved to obtain graphite particles of the desired size. Here, the internal porosity of the graphite particles can be adjusted according to the particle size of the precursor after crushing, the particle size of the precursor in the agglomerated state, etc. For example, the average particle size of the precursor after crushing (the median particle size D50 converted by volume, the same below) is preferably in the range of 12μm to 20μm. In addition, the internal porosity of the graphite particles can also be adjusted according to the amount of volatile components added to the block-shaped molded body. When a part of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as a volatile component. Asphalt can be exemplified as such a binder.

[0031] The graphite particles contained in the second negative electrode mixture layer 32b can be produced, for example, as follows. The coke (precursor) to be the main raw material is crushed into a specified size, and in a state where they are agglomerated using a binder such as asphalt, they are sintered at a temperature above 2600°C, graphitized, and then sieved to obtain graphite particles of a desired size. Here, the internal porosity of the graphite particles can be adjusted according to the particle size of the precursor after crushing, the particle size of the precursor in an agglomerated state, etc. For example, the average particle size of the precursor after crushing is preferably in the range of 12μm to 20μm.

[0032] The ratio (S2 / S1) of the porosity (S2) between the graphite particles in the second negative electrode mixture layer 32b to the porosity (S1) between the graphite particles in the first negative electrode mixture layer 32a is 1.1 to 2.0, preferably 1.1 to 1.7, and more preferably 1.1 to 1.5. If S2 / S1 is less than 1.1, the liquid circulation permeability of the electrolyte deteriorates, and the battery capacity decreases due to repeated rapid charging. In addition, if S2 / S1 exceeds 2.0, the filling density of the second negative electrode mixture layer 32b described later cannot be made approximately the same as the filling density of the first negative electrode mixture layer 32a, and the battery capacity decreases. Here, the porosity between the graphite particles refers to a two-dimensional value calculated based on the ratio of the area of ​​the voids between the graphite particles to the cross-sectional area of ​​the negative electrode mixture layer 32. S2 / S1 is obtained by calculating the void ratio (S1) between graphite particles in the first negative electrode mixture layer 32a and the void ratio (S2) between graphite particles in the second negative electrode mixture layer 32b through the following procedure.

[0033] <Method for measuring the void ratio between graphite particles>

[0034] (1) Exposing the cross section of the negative electrode mixture layer. For example, a method of exposing the cross section includes cutting a portion of the negative electrode and processing it using an ion milling device (eg, IM4000PLUS manufactured by Hitachi High-Tech) to expose the cross section of the negative electrode mixture layer.

[0035] (2) Using a scanning electron microscope, a reflected electron image of the cross section of each of the first negative electrode mixture layer 32 a and the second negative electrode mixture layer 32 b is taken. The magnification for taking the reflected electron image is, for example, 800 times.

[0036] (3) The cross-sectional image obtained as described above is read into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross section in the cross-sectional image is converted into black and the voids in the particle cross section are converted into white.

[0037] (4) In the binary processed images of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b, the voids converted into white, except for the voids inside the graphite particles (pores not connected to the particle surface) and the pores connected to the graphite particle surface with a width of 3 μm or less, are regarded as the voids between the graphite particles, and the area of ​​the voids between the graphite particles is calculated. The void ratio between the graphite particles can be calculated based on the following formula.

[0038] Porosity between graphite particles = area of ​​voids between graphite particles / area of ​​cross section of negative electrode mixture layer × 100

[0039] S1 and S2 are each determined as the average value of three measurements, and S1 / S2 can be calculated based on these values.

[0040] The ratio (D2 / D1) of the packing density (D2) of the second negative electrode mixture layer 32b to the packing density (D1) of the first negative electrode mixture layer 32a is 0.9 to 1.1. By making S2 / S1 satisfy 1.1 to 2.0 and making D2 / D1 within this range, an excellent battery with high capacity and reduced suppression of fast charging cycle characteristics can be obtained. For example, by making the internal porosity of the graphite particles contained in the first negative electrode mixture layer 32a higher than the internal porosity of the graphite particles contained in the second negative electrode mixture layer 32b, S2 / S1 and D2 / D1 can satisfy the above range.

[0041] The packing density (D1) of the first negative electrode mixture layer 32a and the packing density (D2) of the second negative electrode mixture layer 32b can be set to 1.3 g / cm 3~ 2.0g / cm 3 This enables the battery to have a high capacity.

[0042] The packing density of the negative electrode mixture layer 32 refers to the mass of the negative electrode mixture layer 32 per unit volume. First, using the negative electrode 12, the mass of the mixture per unit area of ​​each of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b is measured. In addition, the thickness of each mixture layer of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b is measured based on the cross-sectional image obtained when the interparticle void ratio is calculated. When the thickness of the mixture layer is not stable, 10 points can be measured in the above image, and the average value is used as the thickness of the mixture layer. By dividing the mass of the mixture per unit area by the thickness of the mixture layer, the packing density (D1) of the first negative electrode mixture layer 32a and the packing density (D2) of the second negative electrode mixture layer 32b can be calculated. Based on these values, the ratio (D2 / D1) of the packing density (D2) of the second negative electrode mixture layer 32b to the packing density (D1) of the first negative electrode mixture layer 32a is obtained.

[0043] Next, the specific method for forming the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b is described. For example, first, a negative electrode active material containing graphite particles (hereinafter sometimes referred to as the first graphite particles), a binder and a solvent such as water are mixed to prepare a first negative electrode mixture slurry. Alternatively, a negative electrode active material containing graphite particles different from the first graphite particles (hereinafter sometimes referred to as the second graphite particles) , A binder and a solvent such as water are mixed to prepare a second negative electrode mixture slurry. Then, after the first negative electrode mixture slurry is applied to both sides of the negative electrode collector and dried, the second negative electrode mixture slurry is applied to both sides on the coating formed by the first negative electrode mixture slurry and dried. The first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b are then rolled using a calendering roller, thereby forming a negative electrode mixture layer 32.

[0044] Even if the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b are rolled at the same time as described above, the filling properties of the first graphite particles and the second graphite particles during rolling are not necessarily the same. For example, by changing the particle size distribution of the first graphite particles and the second graphite particles, the filling density of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b can be adjusted. In addition, by making the internal porosity of the second graphite particles lower than the internal porosity of the first graphite particles, the interparticle porosity can be increased without excessively reducing the filling density of the second negative electrode mixture layer 32b. It should be noted that in the above method, after applying the first negative electrode mixture slurry and drying it, the second negative electrode mixture slurry is applied, but the second negative electrode mixture slurry can also be applied after the first negative electrode mixture slurry is applied and before drying. In addition, the second negative electrode mixture slurry can also be applied on the first negative electrode mixture layer 32a after applying the first negative electrode mixture slurry, drying it and rolling it. By changing the rolling conditions of the first negative electrode mixture layer 32 a and the second negative electrode mixture layer 32 b , the respective packing densities can be adjusted more freely.

[0045] At least one of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b may contain a Si-based material. The Si-based material is a material that can reversibly absorb and release lithium ions and functions as a negative electrode active material. Examples of the Si-based material include Si, alloys containing Si, and SiO x (x is 0.8 to 1.6) and other silicon oxides. Si-based materials are negative electrode materials that can increase battery capacity compared to graphite particles. From the perspective of increasing battery capacity and suppressing the reduction of fast charge cycle characteristics, for example, the content of Si-based materials relative to the mass of the negative electrode active material is preferably 1% to 10% by mass, and more preferably 3% to 7% by mass.

[0046] As other materials that can reversibly absorb and release lithium ions, in addition, metals alloyed with lithium such as tin (Sn), or alloys and oxides containing metal elements such as Sn, etc. can also be cited. The negative electrode active material can contain the above-mentioned other materials, and the content of the above-mentioned other materials is preferably less than 10% by mass relative to the mass of the negative electrode active material.

[0047] [positive electrode]

[0048] The positive electrode 11 is composed of, for example, a positive electrode current collector such as a metal foil and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable within the potential range of the positive electrode, or a film having the metal disposed on the surface. The positive electrode mixture layer may include, for example, a positive electrode active material, a binder, a conductive agent, and the like.

[0049] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc., on a positive electrode current collector, drying the mixture to form a positive electrode mixture layer, and then rolling the positive electrode mixture layer.

[0050] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. Examples of lithium transition metal oxides include Li x CoO 2 , Li x NiO 2 , Li x MnO 2 , Li x Co y Ni 1-y O 2 , Li x Co y M 1-y O z , Li x Ni 1- y M y O z , Li x Mn 2 O 4 , Li x M n 2-y M y O 4 、LiMPO 4 , Li 2 MPO 4F (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO 2 , Li x Co y Ni 1-y O 2 , Li x Ni 1-y M y O z (M; Na, Mg, S c , Y, M n 、F e , at least one of Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3) and the like lithium nickel composite oxides.

[0051] Examples of the conductive agent include carbon black (CB), acetylene black (AB), Ketjen black, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0052] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0053] [Spacer]

[0054] For example, a porous sheet having ion permeability and insulation can be used as the spacer 13. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the spacer, olefin resins such as polyethylene and polypropylene, cellulose, etc. are preferred. The spacer 13 can be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can be a multilayer spacer including a polyethylene layer and a polypropylene layer, and a spacer having a material such as an aramid resin or ceramics coated on the surface of the spacer 13 can also be used.

[0055] [Non-aqueous electrolyte]

[0056] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolyte), and can be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent can use, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent can contain a halogen substituted product in which at least a portion of the hydrogen of these solvents is substituted by a halogen atom such as fluorine.

[0057] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.

[0058] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethylethylene. Chain ethers such as 1,2-dimethoxyethane, 1,2-dibutyloxyethane, 1,1-dimethoxymethane, 1,1-diethoxyethane, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0059] As the halogen-substituted product, preferably used are fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP), and the like.

[0060] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF 4 、LiClO 4 、LiPF 6 、LiAsF 6 、LiSbF 6 、LiAlCl 4 、LiSCN、LiCF 3 SO 3 、LiCF 3 CO 2 、Li(P(C2 O 4 )F 4 )、LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, Li 2 B 4 O 7 、Li(B(C 2 O 4 )F 2 ) and other borates, LiN(SO 2 CF 3 ) 2 、LiN(C 1 F 2l+1 SO 2 )(C m F 2m+1 SO 2 ) {l, m is an integer greater than 1} and other imide salts. As for lithium salts, they can be used alone or in combination. Among these, LiPF is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. 6 The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the solvent.

[0061] Example

[0062] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0063] <Example 1>

[0064] [Production of positive electrode]

[0065] As the positive electrode active material, lithium nickel cobalt oxide (LiNi 0.88 Co 0.09 Al 0.03 O 2 ). The positive electrode active material is mixed in an amount of 100 parts by mass, graphite as a conductive agent is 1 part by mass, and polyvinylidene fluoride powder as a binder is 0.9 parts by mass, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode mixture slurry. The slurry is applied to both sides of a positive electrode collector formed of aluminum foil (thickness of 15 μm) by a doctor blade method, and after the coating is dried, the coating is rolled by a calendering roller to produce a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode collector.

[0066] [Preparation of Graphite Particles A]

[0067] The coke was crushed to an average particle size of 17 μm, and pitch was added as a binder to the crushed coke to make it agglomerated. Isotropic pressure was applied to the agglomerate to make a particle size of 1.6 g / cm 3 ~1.9g / cm 3 The block-shaped molded body with a density of . The block-shaped molded body was sintered at a temperature of 2800° C. to graphitize. Next, the block-shaped molded body after graphitization was crushed and sieved using a 250-mesh sieve to obtain graphite particles A with an average particle size of 23 μm.

[0068] [Preparation of Graphite Particles B]

[0069] The coke is crushed to an average particle size of 13 μm, and pitch is added as a binder to the crushed coke to agglomerate the coke to an average particle size of 18 μm. The agglomerate is calcined at a temperature of 2800°C to graphitize, and then sieved using a 250-mesh sieve to obtain graphite particles B with an average particle size of 23 μm. When preparing graphite particles B, the amount of pitch added to the coke is made smaller than the amount of pitch used to prepare graphite particles A, and the average particle size of the agglomerate is adjusted, thereby preparing graphite particles B having a smaller internal porosity than graphite particles A.

[0070] [Production of negative electrode]

[0071] Graphite particles A were mixed in an amount of 95 parts by mass and SiO was mixed in an amount of 5 parts by mass to form negative electrode active material A. Negative electrode active material A: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in an amount of 100:1:1 by mass, and the mixture was kneaded in water to prepare a first negative electrode mixture slurry. In addition, graphite particles B were mixed in an amount of 95 parts by mass and SiO was mixed in an amount of 5 parts by mass to form negative electrode active material B. Negative electrode active material B: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in an amount of 100:1:1 by mass, and the mixture was kneaded in water to prepare a second negative electrode mixture slurry.

[0072] The first negative electrode mixture slurry is applied to both sides of the negative electrode current collector formed of copper foil by a doctor blade method and dried to form a first negative electrode mixture layer. The second negative electrode mixture slurry is then applied to the first negative electrode mixture layer and dried to form a second negative electrode mixture layer. At this time, the coating mass ratio per unit area of ​​the first negative electrode mixture slurry and the second negative electrode mixture slurry is set to 5:5. The first negative electrode mixture layer and the second negative electrode mixture layer are rolled by a calendering roller to produce a negative electrode.

[0073] [Preparation of non-aqueous electrolyte]

[0074] To 100 parts by mass of a non-aqueous solvent prepared by mixing ethylene carbonate (EC) and dimethyl carbonate in a volume ratio of 1:3, 5 parts by mass of vinylene carbonate (VC) was added, and LiPF was added at a concentration of 1.5 mol / L. 6 dissolve and use it as a non-aqueous electrolyte.

[0075] [Fabrication of non-aqueous electrolyte secondary battery]

[0076] (1) After attaching a positive electrode lead to a positive electrode current collector and attaching a negative electrode lead to a negative electrode current collector, the positive electrode and the negative electrode are wound with a separator formed of a polyethylene microporous film interposed therebetween to prepare a wound electrode body.

[0077] (2) Insulating plates are placed above and below the electrode body, respectively, the negative electrode lead is welded to the outer casing, the positive electrode lead is welded to the sealing body, and the electrode body is housed in the outer casing.

[0078] (3) After injecting a nonaqueous electrolyte into the outer casing under reduced pressure, the opening of the outer casing is sealed with a sealing member via a gasket to prepare a nonaqueous electrolyte secondary battery.

[0079] <Example 2>

[0080] The same procedure as in Example 1 was carried out except that the graphite particles B were replaced with the graphite particles C prepared as described below.

[0081] [Preparation of Graphite Particles C]

[0082] The coke is crushed to an average particle size of 12 μm. Pitch is added as a binder to the crushed coke to agglomerate the coke to an average particle size of 18 μm. The agglomerate is calcined at a temperature of 2800°C to graphitize it, and then sieved using a 250-mesh sieve to produce graphite particles C with an average particle size of 23 μm. The amount of asphalt used in making graphite particles C is less than the amount of asphalt used in making graphite particles A, and is greater than the amount of asphalt used in making graphite particles B. In this way, by adjusting the average particle size of the coke and the amount of asphalt, the internal porosity of graphite particles C is lower than the internal porosity of graphite particles A and higher than the internal porosity of graphite particles B.

[0083] <Example 3>

[0084] The same procedures as in Example 1 were carried out except that the coating mass ratio per unit area of ​​the first negative electrode mixture slurry and the second negative electrode mixture slurry was set to 6:4.

[0085] <Example 4>

[0086] The same procedures as in Example 1 were carried out except that the coating mass ratio per unit area of ​​the first negative electrode mixture slurry and the second negative electrode mixture slurry was set to 4:6.

[0087] <Comparative Example 1>

[0088] The same procedure as in Example 1 was carried out except that the graphite particles C were used instead of the graphite particles A, and the graphite particles A were used instead of the graphite particles B.

[0089] <Comparative Example 2>

[0090] The same procedure as in Example 1 was carried out except that a mixture of graphite particles A and graphite particles C at a mass ratio of 1:1 was used instead of the graphite particles A and the graphite particles B.

[0091] [Calculation of the void ratio between graphite particles]

[0092] At an ambient temperature of 25°C, the non-aqueous electrolyte secondary battery of each embodiment and each comparative example was charged to 4.2V at a constant current of 0.2C (920mA), and then charged to C / 50 at a constant voltage of 4.2V. Then, it was discharged to 2.5V at a constant current of 0.2C. The charge and discharge was set as 1 cycle, and 5 cycles were performed. The negative electrode was taken out from the non-aqueous electrolyte secondary battery of each embodiment and each comparative example after 5 cycles, and the porosity between the graphite particles was calculated. The results of each embodiment and each comparative example are shown in Table 1.

[0093] [Determination of Capacity Retention Rate in Rapid Charge Cycle]

[0094] At an ambient temperature of 25°C, the non-aqueous electrolyte secondary battery of each embodiment and each comparative example is charged to 4.2V at a constant current of 1C (4600mA), and then charged to 1 / 50C at a constant voltage of 4.2V. Then, it is discharged to 2.5V at a constant current of 0.5C. The charge and discharge is set as 1 cycle, and 100 cycles are performed. The capacity retention rate of the non-aqueous electrolyte secondary battery of each embodiment and each comparative example in the rapid charge cycle is calculated by the following formula. In addition, the discharge capacity of the first cycle is set as the battery capacity.

[0095] Capacity retention rate = (discharge capacity at the 100th cycle / discharge capacity at the 1st cycle) × 100

[0096] The results of the capacity retention rate and battery capacity in the rapid charge cycle of the non-aqueous electrolyte secondary batteries of each embodiment and each comparative example are summarized in Table 1. In addition, D1, D2, D2 / D1 and S2 / S1 are also shown in Table 1. It should be noted that the higher the value of the capacity retention rate in the rapid charge cycle, the more it indicates that the reduction in the rapid charge cycle characteristics is suppressed and excellent.

[0097] [Table 1]

[0098]

[0099] First layer: first negative electrode mixture layer, second layer: second negative electrode mixture layer

[0100] In the embodiment in which the interparticle porosity of the second negative electrode mixture layer is higher than that of the first negative electrode mixture layer, the rapid charge cycle characteristics are improved. This is believed to be because: by increasing the interparticle porosity of the second negative electrode mixture layer, the electrolyte becomes easy to penetrate from the surface of the mixture layer opposite to the positive electrode toward the collector side, and the electrolyte becomes easy to penetrate into the entire negative electrode mixture layer. In addition, according to the results of Examples 1, 3, and 4, it can be seen that when the coating mass per unit area is more in the first negative electrode mixture layer than in the second negative electrode mixture layer, the rapid charge cycle characteristics are improved. This is believed to be because the amount of electrolyte that penetrates into the negative electrode mixture layer becomes most appropriate. In addition, it was confirmed that high-capacity batteries were obtained in Examples 1 to 4.

[0101] Description of Reference Numerals

[0102] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 outer body, 16 sealing body, 17, 18 insulating plates, 19 positive electrode lead, 20 negative electrode lead, 21 groove portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cover, 26a opening portion, 27 gasket, 30 negative electrode collector, 32 negative electrode mixture layer, 32a first negative electrode mixture layer, 32b second negative electrode mixture layer.

Claims

1. A non-aqueous electrolyte secondary battery comprising a negative electrode, the negative electrode comprising: a negative electrode current collector, a first negative electrode mixture layer provided on a surface of the negative electrode current collector, and a second negative electrode mixture layer provided on a surface of the first negative electrode mixture layer, The first negative electrode mixture layer and the second negative electrode mixture layer are formed by applying a negative electrode mixture slurry containing graphite particles. The amount of the negative electrode mixture slurry applied per unit area of ​​the first negative electrode mixture layer is greater than the amount of the negative electrode mixture slurry applied per unit area of ​​the second negative electrode mixture layer. The ratio S2 / S1 of the void ratio S2 between the graphite particles in the second negative electrode mixture layer to the void ratio S1 between the graphite particles in the first negative electrode mixture layer is 1.39 to 2.0, A ratio D2 / D1 of the packing density D2 of the second negative electrode mixture layer to the packing density D1 of the first negative electrode mixture layer is greater than or equal to 0.9 and less than 1.

01.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein A ratio S2 / S1 of the void ratio S2 between the graphite particles in the second negative electrode mixture layer to the void ratio S1 between the graphite particles in the first negative electrode mixture layer is 1.39 to 1.

7.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The packing density D1 of the first negative electrode mixture layer and the packing density D2 of the second negative electrode mixture layer are 1.3 g / cm 3 ~2.0g / cm 3 .

4. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein At least one of the first negative electrode mixture layer and the second negative electrode mixture layer contains a Si-based material.

Citation Information

Patent Citations

  • Lithium secondary battery and its manufacturing method

    JP2003077463A

  • Electrode for electochemical battery, its manufacturing method, and electochemical battery using the same

    JP2006196457A

  • Negative electrode for lithium secondary battery and lithium secondary battery containing the same

    JP2015511389A

  • Nonaqueous electrolyte secondary battery

    JP1999214042A

  • Nonaqueous secondary battery, electrode, method of manufacturing nonaqueous secondary battery, and method of manufacturing electrode

    JP2007214038A